Global business today - Hill, Charles W. L; Udayasankar, Krishna; Chow, Hou Wee (McGraw-Hill Education, 2014)
Provides insightful illustrations in every chapter, interesting anecdotes have been carefully weaved into the narrative of the text to engage the reader. This title includes new country focus boxes that provide background on the political, economic, social, or cultural aspects of countries grappling with an international business issue